2022
DOI: 10.1111/1755-6724.14942
|View full text |Cite
|
Sign up to set email alerts
|

Multisphere Tectonics of the Earth System

Abstract: The fundamental theoretical framework of the Multisphere Tectonics of the Earth System is as follows: (1) It intends to extend the geotectonic studies from the crustal and lithospheric tectonics to the multisphere tectonics of the Earth system as a whole. (2) The global dynamics driven by both the Earth system and the cosmic celestial system: solar energy, multispheric interactions of the Earth system and the combined effects of the motions of celestial bodies in the cosmos system are the driving forces of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…It is generally believed that there developed five periods of different scale pre‐Devonian tectono‐thermal events in the South China Block, from 1900–1800 Ma, 1000–900 Ma, 850–780 Ma, 650–500 Ma to 440–420 Ma, respectively. The interpretations of these tectono‐thermal events have long been controversial (Faure et al, 2018; Grabau, 1924; Guo et al, 1963, 1965; Huang, 1945; Lin, Xing, Davis, Wu, et al, 2018; Lin, Xing, Davis, Yin, et al, 2018; Ma et al, 1961; Ren, 1964; Shu et al, 2009, 2011, 2014, 2015, 2018, 2020, 2021; Shu, Deng, et al, 2008; Shu, Faure, et al, 2008; Shui, 1988). The Cathaysia Block was proposed to show clearly intracontinental orogenesis since the Neoproterozoic for a long time (e.g., Faure et al, 2018; Ren & Li, 2016; Shu et al, 2018, 2020, 2021; Zhang et al, 2013).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally believed that there developed five periods of different scale pre‐Devonian tectono‐thermal events in the South China Block, from 1900–1800 Ma, 1000–900 Ma, 850–780 Ma, 650–500 Ma to 440–420 Ma, respectively. The interpretations of these tectono‐thermal events have long been controversial (Faure et al, 2018; Grabau, 1924; Guo et al, 1963, 1965; Huang, 1945; Lin, Xing, Davis, Wu, et al, 2018; Lin, Xing, Davis, Yin, et al, 2018; Ma et al, 1961; Ren, 1964; Shu et al, 2009, 2011, 2014, 2015, 2018, 2020, 2021; Shu, Deng, et al, 2008; Shu, Faure, et al, 2008; Shui, 1988). The Cathaysia Block was proposed to show clearly intracontinental orogenesis since the Neoproterozoic for a long time (e.g., Faure et al, 2018; Ren & Li, 2016; Shu et al, 2018, 2020, 2021; Zhang et al, 2013).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The interpretations of these tectono‐thermal events have long been controversial (Faure et al, 2018; Grabau, 1924; Guo et al, 1963, 1965; Huang, 1945; Lin, Xing, Davis, Wu, et al, 2018; Lin, Xing, Davis, Yin, et al, 2018; Ma et al, 1961; Ren, 1964; Shu et al, 2009, 2011, 2014, 2015, 2018, 2020, 2021; Shu, Deng, et al, 2008; Shu, Faure, et al, 2008; Shui, 1988). The Cathaysia Block was proposed to show clearly intracontinental orogenesis since the Neoproterozoic for a long time (e.g., Faure et al, 2018; Ren & Li, 2016; Shu et al, 2018, 2020, 2021; Zhang et al, 2013). However, new research and new data argue that a multi‐terrane accretion‐collision model can readily explain the five tectono‐thermal events and better understanding for the assembly of the Cathaysia Block (e.g., Lin, Xing, Davis, Wu, et al, 2018; Lin, Xing, Davis, Yin, et al, 2018; Liu et al, 2021).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geomorphic evolution of a region is a direct expression of the Earth's deep dynamic action on the surface and is highly significant for understanding the relationship between tectonic deformation and surface erosion (Jolivet et al, 2010;Dong et al, 2015;Liu et al, 2015a;Ren et al, 2022;Zhu et al, 2022). The Huangling Massif in northern South China is a crucial geomorphological barrier for the Yangtze River flowing into the East China Sea (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the Cathaysia Block had a metamorphic basement dominated by Palaeoproterozoic and Mesoproterozoic crust (Gan & Zhuang, 1993; Qin et al, 2006; Shui, 1987; Wang et al, 1992; Yu et al, 2006; Zhao, 1999). Recent studies indicate that the Palaeoproterozoic and Mesoproterozoic metamorphic basement is Neoproterozoic and Cambrian in age, and geochemical evidence suggests that the Cathaysia block may be a Caledonian orogenic belt (Charvet et al, 2010; Li et al, 2010; Ren & Li, 2016; Sun, 1954; Shu et al, 2014; Xu et al, 1987; Zhao et al, 2019, 2021). Other researchers theorize that the Cathaysia Block was composed of multiple terranes, with the development of multi‐island ocean systems between these terranes from the Neoproterozoic to the early Paleozoic (Chen and Xiao, 1998; Dong et al, 2016; Ge et al, 2019; He et al, 2014; Jiang et al, 2018; Jiang et al, 2020; Lin et al, 2018; Ma, 2006; Peng et al, 2016a, 2016b; Yin et al, 1999; Zhang et al, 2015, 2018).…”
Section: Introductionmentioning
confidence: 99%